2007
DOI: 10.1016/j.firesaf.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A study of portable water mist fire extinguishers used for extinguishment of multiple fire types

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 12 publications
(14 reference statements)
0
37
0
2
Order By: Relevance
“…The temperature kept decreasing until total extinction for the continuous discharging of water mist. Photographs of the tests showed that once the wood was contacted with water mist, the flame was controlled and not any flare up was observed, different to that seen in liquid pool fires [15]. Much smoke was produced, but the room clear up soon after the fire was fully extinguished.…”
Section: Suppression Testsmentioning
confidence: 86%
See 1 more Smart Citation
“…The temperature kept decreasing until total extinction for the continuous discharging of water mist. Photographs of the tests showed that once the wood was contacted with water mist, the flame was controlled and not any flare up was observed, different to that seen in liquid pool fires [15]. Much smoke was produced, but the room clear up soon after the fire was fully extinguished.…”
Section: Suppression Testsmentioning
confidence: 86%
“…Experiments on extinguishing wood crib fires are reported by Liu and coworkers [15]. But only with relatively high pressure and long time discharging could extinguish the fires.…”
Section: Introductionmentioning
confidence: 99%
“…The slower combustion rate means less product formation and heat generated, which results in flame temperature decrease and so on. For the water mist, the fire suppression mechanisms of water mist include at least three aspects [17,18] : (i) Gas phase and fuel surface cooling; (ii) Local and global oxygen depletion; (iii) Radiant heat blocking to surroundings and fuel surface.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, experiments have shown that boil-over or spillage is not present when water mist is discharged into the oil at high temperature (greater than 300°C), while it is observed if oil temperature is relatively low (almost 200°C). The same authors have also carried out an experimental and theoretical research on portable water-mist systems with respect to a variety of fire scenarios [52]. Among these latter, flammable liquids, cooking oil and wood cribs stand as the most interesting applications.…”
Section: Additional Studiesmentioning
confidence: 99%